The Turn‐of‐the‐Year in Canada - BERGES, ANGEL; McCONNELL, JOHN J.; SCHLARBAUM, GARY G. (Journal of Finance, 1984)
ABSTRACT A number of investigators have reported that January stock returns in the U.S. exceed returns for other months of the year. This paper documents a similar finding for Canadian stocks over the period 1951–1980. However, Canada did not introduce a capital gains tax until 1973 and the paper reports that January returns in Canada exceed returns for other months of the year before and after this date. Thus, these data do not support the tax‐loss‐selling‐pressure hypothesis as the entire explanation for the turn‐of‐the‐year effect in stock returns, nor, by implication, do they support the tax‐loss‐selling‐pressure hypothesis as the complete explanation for the “small firm” effect in U.S. stocks returns.